91 Management and Outcomes of Appendicitis in The Pre-COVID-19, COVID-19 And Post-COVID-19 Periods. (12th October 2021) - Abeywickrema, M; Patel, C; Ghumman, A K; Krishan, A; Puventhiranathan, P; Mae Kelly, G; Nijjar, R
Abstract: Aim: The COVID-19 pandemic resulted in an upheaval of national surgical guidance on appendicitis, which has previously favoured surgical over conservative approaches. We analysed how these guidelines altered management and outcomes of appendicitis. Method: A retrospective cohort study at Heartlands Hospital, Birmingham of all appendicitis admissions around and during the first COVID-19 peak was conducted, with analysis of electronic patient records using the acute surgical worklist. Results: 48 admissions for appendicitis during the two-month period from 01/02/20 to 25/03/20 prior to the COVID-19 peak and 28 admissions in the two months during the peak itself from 30/03/20 to 24/05/20 were identified. Prior to the COVID-19 peak, a lower proportion of cases was managed conservatively (18.8%) compared to the latter (67.9%, p < 0.0001 ). This change also coincided with a switch from laparoscopic to open approaches in those managed surgically. We studied a further period post-COVID-19 peak from 01/06/20 to 26/07/20, where proportions of patients managed conservatively versus surgically did not significantly change following the COVID-19 peak, although surgical preference reverted from open to laparoscopic approaches. During the COVID-19 period, a reduced length of stay was seen in cases managed conservatively (1.65 days) compared to those managed surgically (4 days, p = 0.024 ). Differences in readmission rates were not statistically significant. Conclusions: A reduction in numbers of appendicitis presentations as well as a switch to conservative approaches was seen during COVID-19. These findings furthermore support non-inferiority of conservative over open surgical approaches in most appendicitis cases at a time where laparoscopy was deemed unfeasible.